2016
DOI: 10.1111/wvn.12163
|View full text |Cite
|
Sign up to set email alerts
|

Implementation Strategies for Same Day Discharge Post Percutaneous Coronary Intervention: An Integrative Review

Abstract: The results of this integrative review inform our understanding of how same day discharge is operationalized and what strategies can be used to implement same day discharge. The findings of the review highlight that there is a need for more research examining implementation strategies in a detailed manner that can assist others to introduce and sustain same day discharge in routine practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Implementation of an SDD program has been estimated to save hospitals $3000–$6000 per case, resulting in savings of $108,000 to $216,000 per every 100 elective PCIs for hospitals operating in the 75th percentile of SDD 41 . An integrative review by Chen et al 22 found that guidelines, environment, education, audit, or feedback were important strategies for the success of SDD programs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Implementation of an SDD program has been estimated to save hospitals $3000–$6000 per case, resulting in savings of $108,000 to $216,000 per every 100 elective PCIs for hospitals operating in the 75th percentile of SDD 41 . An integrative review by Chen et al 22 found that guidelines, environment, education, audit, or feedback were important strategies for the success of SDD programs.…”
Section: Discussionmentioning
confidence: 99%
“…13,15 The 2009 consensus document from the Society for Cardiovascular Angiography and Interventions (SCAI) released criteria for SDD, 16 which we followed in the development of our SDD program. Over time, several randomized and observational studies demonstrated the safety of SDD in high-risk patient subgroups, 15,[17][18][19][20][21][22][23][24][25] which led to a change in the recommendations and definition of high-risk PCI. 26 New guidelines have also been developed to determine which patients are considered safe for SDD.…”
Section: Introductionmentioning
confidence: 99%
“…10 While the evidence for the safety and effectiveness of SDD is well described in the literature, there is little reported which can be used to help guide the implementation of SDD within complex healthcare systems. 11…”
Section: Introductionmentioning
confidence: 99%
“…Although SDD has been shown to be safe and feasible, [5][6][7] its uptake within health services worldwide has been variable. While there is a growing body of literature describing the impact of SDD on patient and health service outcomes, [5][6][7][8] the process of implementing SDD has not been well described in literature and there is little information available 9 to inform clinicians wanting to implement this model of care. To address this gap in the literature, we undertook this process evaluation study aimed to evaluate the implementation of SDD as a new model of care in the cardiac service of an Australian tertiary teaching hospital.…”
Section: Introductionmentioning
confidence: 99%